Biotransformation of magnetic nanoparticles as a function of coating in a rat model. Issue 39 (18th September 2015) - Ruiz, A.; Gutiérrez, L.; Cáceres-Vélez, P. R.; Santos, D.; Chaves, S. B.; Fascineli, M. L.; Garcia, M. P.; Azevedo, R. B.; Morales, M. P.
Abstract : AC susceptibility data show that DMSA and PEG coated magnetic nanoparticles after i.v. in rats quickly transform into ferritin. Abstract : Long-term in vivo studies in murine models have shown that DMSA-coated nanoparticles accumulate in spleen, liver and lung tissues during extended periods of time (at least up to 3 months) without any significant signs of toxicity detected. During that time, nanoparticles undergo a process of biotransformation either by reducing the size or the particle aggregation or both. Using a rat model, we have evaluated the transformations of magnetic nanoparticles injected at low doses. Particles with two different coatings, dimercaptosuccinic acid (NP-DMSA) and polyethylene glycol (NP-PEG-(NH2 )2 ) have been administered to animals, to evaluate the role of coating in the degradation of the particles. We have found that low doses of magnetic nanoparticles are quickly metabolized by the animals. In fact, using a nanoparticle dose four times lower than in previous experiments, NP-DMSA were not observed 24 h after the administration either in the liver or in the lungs. Interestingly, an increased amount of ferritin, the iron storage protein, was observed in liver tissues from rats that were treated with the low dose of NP-DMSA in comparison with the control ones, suggesting a rapid metabolization of the particles into ferritin iron. On the other side we have found that, NP-PEG-(NH2 )2 are still detectable in several organs 24 h after their administration at low doses. Probably, due to the longer circulation times of the NP-PEG-(NH2 )2, there is a delay in the arrival of the particles to the tissue and this is the reason why we are able to see the particles 24 h post-administration. PEG coating could also be protecting the nanoparticles from rapid degradation of the reticuloendothelial system. Knowledge on the biodistribution, circulation time and degradation processes is required to gain a better understanding of the safety evaluation of this kind of nanomaterial for biomedical applications.